Contagion and regulation in endogenous bank networks - Keiserman, Bernardo (2014)
We develop a simple model of endogenous bank networks to study financial contagion and how leverage regulation may affect it. Banks maximize expected profit by choosing the optimal allocation of resources between three different classes of assets. An interbank network arise as result of loans between banks, creating a direct channel of contagion in the financial system. Contagion may occur when the realized return of the risky asset is sufficiently low to make a bank insolvent, subsequently triggering a cascade effect that propagates through default in interbank loans. Contrary to what would be expected, our results show that despite forcing banks to deleverage, increasing minimum capital requirements may lead to a system with higher aggregate levels of default.